IMMUONOLOGICAL AND BIOCHEMICAL EVALUATION OF AVIAN INFLUEZA VACCINES SUPPLEMENTED WITH CHROMIUM IN LAYERS - M. F. Talib; A. H. Ulaiwi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate the immune response of the vaccinated chickens through avian influenza virus antibody (AIV-Ab) titers as well as evaluate liver function. The study measure of immunological parameters, namely the hemaglutinine inhibition test (HI) and a biochemical parameter called the liver function test, as well as a comparison between the highly pathogenic avian influenza (HPAI) recombinant (rH5N1) vaccine and the classical (cH5N8) vaccine. The study was designed as follows: G1: given rH5N1 vaccine only; G2: given cH5N8 only; G3: given rH5N1 with Cr III supplement; G4: given cH5N8 with Cr III supplement; G5: given Cr III supplement; G6: negative control with no vaccination or supplementation. The titer of AIV-Ab at 21 days old showed a significant increase in G3 as compared with other groups. At 42 and 60 days old, G3 and G4 revealed the highest levels as compared with another groups. The results of ALT enzyme levels at 30 and 60 days old showed the lowest levels in G3 and G5 as compared to other groups. Additionally, there was a significant decrease in AST enzyme levels in all groups except G6 at both ages 30 and 60 days old. In conclusion, Cr III supplementation can improve the immune response against AI vaccines and has a positive impact on liver health.